Review of Charaka Samhita Nidana Sthana - Kaushik, Kavita; Aggarwal, Ruby Rani (International Research Journal of Ayurveda & Yoga, 2021)
The basic principle in Ayurveda “rogamado nirakshte tatoanantram aushadham” means we understand the disease at first and then choose the drugs. Charaka Samhita, the main treatise of Agnivesha is the most ancient representative of medicine. Nidana sthana is given special importance in Charaka Samhita as per Sarva Tantra Siddhant i.e. Karya Karan Bhav which means the effect always imitate the cause. It is a bridge between initial phase i.e. origin to final outcome i.e. treatment of disease. The complete knowledge regarding the origin to pathogenesis helps to institute appropriate treatment and to suggest preventive measures. This paper is about Nidana sthana of Charaka Samhita. Nidana Sthana is the second section of Charaka Samhita among eight sections. This section deals with the principle diagnosis of eight diseases both on the basis of mythological historical facts and also clinical examinations.